2017
DOI: 10.1021/acs.biochem.7b00020
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Structure and Oligomerization of Major Royal Jelly Protein 1 (MRJP1) by Mass Spectrometry and Complementary Biophysical Tools

Abstract: Royal jelly (RJ) triggers the development of female honeybee larvae into queens. This effect has been attributed to the presence of major royal jelly protein 1 (MRJP1) in RJ. MRJP1 isolated from royal jelly is tightly associated with apisimin, a 54-residue α-helical peptide that promotes the noncovalent assembly of MRJP1 into multimers. No high-resolution structural data are available for these complexes, and their binding stoichiometry remains uncertain. We examined MRJP1/apisimin using a range of biophysical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 83 publications
(292 reference statements)
1
43
0
Order By: Relevance
“…As MRJP1 and apisimin form in RJ a complex with a stoichiometry of 4:4 (Mandacaru et al, ; Tian et al, ) and as relative transcript abundance is similar for both genes (Figure ), one would expect to quantify approximately the same molar amount of apisimin as MRJP1 at least in the HG at day 8. However, within the present study apisimin was not detected at all.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…As MRJP1 and apisimin form in RJ a complex with a stoichiometry of 4:4 (Mandacaru et al, ; Tian et al, ) and as relative transcript abundance is similar for both genes (Figure ), one would expect to quantify approximately the same molar amount of apisimin as MRJP1 at least in the HG at day 8. However, within the present study apisimin was not detected at all.…”
Section: Resultsmentioning
confidence: 98%
“…As MRJP1 and apisimin form in RJ a complex with a stoichiometry of 4:4 (Mandacaru et al, 2017;Tian et al, 2018) and as relative transcript abundance is similar for both genes (Figure S3) (Table S6). Within the brain, only MRJP1 was found within the 20 most abundant proteins at day 8 (37.8 ± 9.8 fmol; 5th place) (Table S6).…”
Section: Protein Amountsmentioning
confidence: 90%
See 1 more Smart Citation
“…This difference in pH is known to affect the structure of the most abundant protein in RJ, MRJP1, which can be isolated from RJ as a monomer (monoMRJP1) and as an oligomer (oligoMRJP1) [10][11][12][13]. At neutral pH, oligoMRJP1 forms a tetramer in complex with four molecules of apisimin, a small 54-amino-acid-comprising protein that is also present in RJ [14,15]. At pH 4.0, oligoMRJP1 is organized into higher-level oligomers and/or polymers of unknown structure [10].…”
Section: Resultsmentioning
confidence: 99%
“…The author found that MRJP-1 multimer was stable at 2°C or À18°C. According to the most recent findings, the core structure of the MRJP1 multimer consists of four molecules of MRJP1, four molecules of the peptide apisimin [34] and, surprisingly, eight molecules of 24-methylenecholesterol [35,36].…”
Section: Comparison Of Mrjp-1 Multimer and 10-hda Contents In Rj Sampmentioning
confidence: 99%